2010
DOI: 10.4111/kju.2010.51.10.713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Possible Predictive Variables for the Outcome of Shock Wave Lithotripsy of Renal Stones

Abstract: PurposeThe aim of this study was to evaluate possible predictive variables for the outcome of shock wave lithotripsy (SWL) of renal stones in a single center.Materials and MethodsBetween March 2008 and March 2010, a retrospective review was performed of 115 patients who underwent SWL for solitary renal stones. The patients' characteristics and stone size, location, skin-to-stone distance (SSD), and Hounsfield units (HU) of stone were reviewed. The impact of the possible predictors on the disintegration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The same ratio was also reported by Bozkurt, Wiesenthal, Chung, Keshvari, and El-Nahas [5,[10][11][12][13], and an almost identical one by Junuzovic [14]. The Chi-square test showed no significant differences between the male and female patients in the success rate of ESWL, which was consistent with the finding of Tavakkoli [15]; whereas, Gupta and Park reported a higher rate of ESWL success in male patients [8,16]. The overall success rate of ESWL in the present study was 71%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The same ratio was also reported by Bozkurt, Wiesenthal, Chung, Keshvari, and El-Nahas [5,[10][11][12][13], and an almost identical one by Junuzovic [14]. The Chi-square test showed no significant differences between the male and female patients in the success rate of ESWL, which was consistent with the finding of Tavakkoli [15]; whereas, Gupta and Park reported a higher rate of ESWL success in male patients [8,16]. The overall success rate of ESWL in the present study was 71%.…”
Section: Discussionsupporting
confidence: 89%
“…However, different success rates have been reported in various studies. For example, the overall success rate reported in the studies carried out Abdel, Park, Saeidi, and Murota-Kawano were 87, 68.7, 55, and 94.5%, respectively [8,[17][18][19]. Moreover, Jee reported a 90.9% overall success rate in the treatment of renal stones in children [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found no significant correlation between stone size and the stone-free rate. However, stone size has been reported in other studies as a significant predictor of the results of ESWL [17,19,20]. This is because of different stone characteristics such as stone density and location.…”
Section: Discussionmentioning
confidence: 93%
“…Hounsfield Units has commonly been reported to be a significant factor in shock-wave lithotripsy (23). Chung et al reported a statistical difference between successful and unsuccessful ESWL (675.29 versus 1075.00, respectively).…”
Section: Discussionmentioning
confidence: 99%